Preaching Wisdom to the Three Treatises - Patmury, J (Journal of Dharma, 2001)
Roberto de Nobili, Preaching Wisdom to the Three Treatises, translated and introduced by Anand Amaladass and Francis X. Cloony, St. Louis: The Institute of Jesuit Sources, 2000, pp.xxi+345.